A study on accuracy of linear ball guide. (April 2022) - Zhang, Penghai; Wang, Tao; Zha, Jun
The accuracy of linear motion guide greatly affects the form accuracy of the processed parts in precision machine tools. For the linear ball guide, it is an important issue that how to improve accuracy by optimizing structure parameters based on the geometric errors. Due to the diversity of geometric errors and structure parameters, it requires a quantitative indicator of error averaging ability to judge whether a linear ball guide has higher accuracy. In this article, based on the newly built accuracy model and the newly defined averaging coefficient, the influence of rail profile errors and deformation errors on the error motions in five degrees of freedom can be quantitatively studied for the guides with one row of balls, one block and four blocks. It finds that, both the straightness and angular accuracies increase as the number of contact balls increases. For the guides with one and four blocks, the profile errors with integer wave numbers have main influence on the straightness and primary angular (around the moving direction) error motions, while those near both sides of integer wave numbers have main influence on the supporting angular error motions. The influence of deformation errors on accuracy coincides with that of profile errors. The accuracy model discussed can be conveniently used to predict error motions, select optimized number of contact balls and select optimized spacing of adjacent mounting holes in the design process of linear ball guide.